Enhanced thermoelectric performance of chalcopyrite nanocomposite via co-milling of synthetic and natural minerals - Balaz, Peter; Dutkova, Erika; Levinsky, Petr; Daneu, Nina; Kubickova, Lenka; Knizek, Karel; Balaz, Matej; Navrátil, Jiří; Kašparová, Jana; Ksenofontov, Vadim; Moeller, Angela; Hejtmanek, Jiri (Elsevier Science BV, 2020)
Chalcopyrite CuFeS2 was shown to be a promising thermoelectric material. Considering thermoelectric efficiency, its relatively high and temperature weakly dependent power factor, economic affordability and ecological benignity is counterbalanced by a high lattice thermal conductivity. Thus it is highly desirable to lower the thermal conductivity of chalcopyrite thermoelectric material without deterioration of other thermoelectric characteristics. In our study, we demonstrate that mechanosynthesis followed by appropriate sintering enables to prepare such nanostructured ceramics with a favourable thermoelectric response. Our study shows that mechanosynthesis is a low-cost technological route for the production of thermoelectric chalcopyrite ceramics.
Zvýšená termoelektrická účinnost chalkopyritového nanokompozitu pomocí společného mletí syntetických a přírodních minerálů
Keywords: chalcopyrite; nanocomposites; mechanochemistry; thermoelectrics; chalcopyrit; nanokompozity; mechanochemie; termoelektřina